Tyrosinase Inhibitory Activity of Major Fractions of Quercus Infectoria Galls - Sharifi far, Fariba; Dehghan-Nudeh, Gholamreza; Raeiat, Zeinab; Amirheidari, Bagher; Moshrefi, Mandan; Purhemati, Amin (Pharmacognosy Communications)
Objective: Our previous studies have shown high tyrosinase inhibitory effect of Quercus infectoria galls, an endemic plant to Iran. Considering the potency of tyrosinase inhibitors in cosmetic as a skin depigmentation and lightening agent, we have studied the Q. infectoria galls, and its major fractions for tyrosinase-inhibitory activity. Materials and methods: A methanolic extract of Q. infectoria galls was evaporated in vacuum. The resulting residue was suspended in water and extracted successively with a combination of petroleum ether, chloroform, ethyl acetate and methanol in increasing order of polarity. As a result, fractions 1–18 were obtained. The fractions were initially screened for the O-diphenolase inhibitory activity of tyrosinase using L-tyrosine as a substrate on TLC plate by the bioautography method. All the active inhibitors from the fi rst test were dissolved in methanol to give different concentrations. 80 microliter of L-tyrosine (0.5mM) was added to wells containing a 50 μl sample, and incubated for 10 minutes at room temperature. Seventy μl of mushroom tyrosinase (1000 units/ml) was added and incubated again for 10 min at 35°C. The enzyme reaction was monitored by measuring the change in absorbance at 475 nm (at 37°C) for 10 and 20 min after incubation. The percent of inhibition of the enzyme was measured and IC 50 values of each sample were calculated by probit analysis. Results: Amongst the separated fractions, fractions V and VЦ separated in ethyl acetate-methanol exhibited the highest inhibition of mushroom tyrosinase (89.2% and 93.65% inhibition respectively) in comparisonto kojic acid (96.54% inhibition). The least IC 50 values were due to fractions of V and VЦ (IC 50 values of 12.0 and 8.0 μg/ml respectively). The total extract induced 86.34% inhibition with IC 50 value of 42.0 μg/ml (kojic acid with IC 50 = 2.7 μg/ml). Conclusion: Our fi ndings indicated that the fractions with potent antityrosinase effect were extracted in the ethyl acetate-methanol fraction, so may have semi-polar nature like gallic acid and/or ellagic acid or might be from fl avonoids. The confi rmation of this needs further fractionation which is the subject of further study in our laboratory.
Keywords: Fractionation; Quercus infectoria galls; Tyrosinase inhibition; Phenolic acids